What Have We Learned From a Decade of Manufacturing Enterprise Surveys in Africa? - Bigsten, Arne; Söderbom, Måns (World Bank, Washington, DC, 2012)
In the early 1990s the World Bank launched the Regional Program on Enterprise Development in several African countries, a key component of which was the collection of manufacturing firm-level data. In this paper the authors review the research based on the data sets generated by these and subsequent firm surveys in Africa, with a special view to what they think are the most important policy implications. The authors survey the research on the African business environment, focusing on market size, risk, access to credit, labor, and infrastructure. They cover the research on how firms choose to organize themselves and how firms do business. They review the research on firm performance, including firm growth, investment and technology acquisition, and exports. They conclude with an extended discussion of the policy lessons.